Om Grundtvig-Selskabet 1947-1997 - et tilbageblik - Michelsen, William (Grundtvig-Studier, 1997)
About the Grundtvig Society - a Retrospective View By William Michelsen From the outset the intention was that the Grundtvig Society should be an open, scholarly society, consisting of about 25 bona fide Grundtvig scholars, who make up its executive committee, and app. 500 members. Anybody interested may become a member of the society and receives the Society’s yearbook, Grundtvig Studies, for his subscription fee. The decision to found the society of that name and structure was first taken at a meeting of Grundtvig scholars in Ribe, to which Bishop C.I. Scharling and Dean Villiam Grønbæk had invited Vicar Henning Hoirup as well as three Masters of Arts, Steen Johansen (Grundtvig bibliographer), Helge Toldberg and William Michelsen. The meeting had only intended to provide an opportunity for these scholars to exchange information about their research work, but during the meeting it became clear that there was a need for a learned society for a much wider circle of people with an interest in Grundtvig: not only a wider circle of Grundtvig scholars, but also a public for the research work, large or small, of these scholars. With this purpose in mind, a first general assembly was held in January 1948 at Vartov in Copenhagen. In the meantime the 6 Grundtvig scholars mentioned above had contacted a further number of Grundtvig scholars; they called the meeting at Vartov where the statutes of the Society were agreed, and where the the elections of chairman, vice-chairman, editor of Grundtvig Studies, and treasurer took place. The first chairman of the Society was C. I. Scharling and after his death in 1951 Henning Høirup, who held the post until 1972 when the vice-chairman took over the appointment. 7 years later Christian Thodberg took up the post as chairman, and on his retirement in November 1990 Peter Balslev-Clausen was elected in his place. The first editor of Grundtvig Studies was Henning Høirup, who, after he had been elected chairman, was followed by Gustav Albeck, who remained editor until his death in 1995. More recently the editorial staff has included William Michelsen, Hellmut Toftdahl (who wished to retire as a member of the staff in 1995), Jens Holger Schjorring, Flemming Lundgreen-Nielsen and Kim Arne Pedersen. The activities of the Society - besides the annual meetings and the publication of Grundtvig Studies - have consisted mainly in the preparation of a complete ≫Registrant of N.F.S.Grundtvig Papers≪ I-XXX, Copenhagen 1957-1964, in cooperation with the Danish Language and Literature Society, and a large number of ≫Writings published by the Grundtvig Society≪ which, in most cases, the members have been able to buy at a reduced price. In addition, the Society has published a series of Grundtvig’s writings with commentaries. The main purpose of the Society, the publication of a complete edition of Grundtvig’s works is such an immense task that it can only be accomplished in the same way as the Grundtvig Registrant, i.e. by a team-work of scholars receiving public support. On November 1st 1988, the Centre of Grundtvig Studies at the University of Aarhus began its work, and as one of many activities it arranged an international Grundtvig conference at Sandbjerg Manor House near Sønderborg in September 1989. On this occasion the Grundtvig Society and the Grundtvig Centre agreed to cooperate about the publication of Grundtvig Studies. This cooperation has led to a much expanded study of Grundtvig’s writings, the results of this scholarship being regularly published in the yearbook.